Expression of Cd31, Cd34 and tryptase in potentially malignant lesions and squamous cell carcinoma - Carolina Rodrigues TeÃfilo (2012)
Angiogenesis is the development of new blood vessels from pre-existing capillaries, being an essential step in tumor growth for supplying nutrition and oxygen to cells in proliferation. A cell that may be involved in this process is the mast cell (MC), since besides the defense function, acts in the blood vessels regulation. The MC participation in the induction of angiogenesis has been suggested in various malignant tumors. The purposes of this study was to evaluate angiogenesis and mast cell density in oral epithelial dysplasia and squamous cell carcinoma (SCC). This is an observational, retrospective and quantitative study using the sample selection from the archives of the Department of Legal Medicine and Pathology and Laboratory of Oral Pathology, both from the Federal University of CearÃ. For MC evaluation , the sample was consisted of 73 paraffin blocks, distributed between SCC (n=30), epithelial dysplasia (n=23) and hyperplasias fibroepithelial (HFE) (n = 20), as control, and for angiogenesis the sample was 65 blocks, consisted of 24 SCC, 19 epithelial dysplasias and 22 HFE. Immunohistochemistry was performed using the MC-tryptase, CD31 and CD34 antibodies. For quantification, digital images were captured and then counting was performed using Image J software. The antibody staining percentage was determined using SAMM software. With regard to mast cells, there was a lower density in malignant lesions in relation to HFE and dysplasia (p = 0.0092). Evaluating angiogenesis, CD31 expression showed differences between epithelial dysplasia and SCC and between SCC and HFE, with a greater percentage of vessels in SCC (p <0.0001). However, CD34 expression did not differ between groups. The CD31 antibody was shown to be a better angiogenesis marker in oral mucosa than CD34. Increased vascularity in oral squamous cell carcinoma suggests that angiogenesis is necessary for tumor growth, increasing when the malignant transformation starts. However, no correlation was found between mast cells and angiogenesis.